2012
DOI: 10.1590/s0104-42302012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the concordance rates between core needle biopsy and surgical excision in patients with breast cancer

Abstract: The results of this study indicate that the immunohistochemical analysis of ER, PR, Ki-67, and p53 from core biopsy specimens provided results that accurately reflect the marker status of the tumor. The concordance rate of HER2 was less consistent; although it produced substantial concordance, values were very close to moderate concordance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
3
11
2
Order By: Relevance
“…A 23% reduction in the mean Ki-67 proliferative index was observed in the post-treatment tumor (Mean +/– SEM: 10% +/– 1.0) compared to the pre-treatment tumor (Mean +/– SEM: 13% +/– 0.5) ( p = 0.02) (Figure 3B). Given that substantial concordance has been reported for the Ki-67 index between breast cancer core needle biopsies and their respective final surgical specimen [37], we believe this propranolol-mediated statistically significant decrease in tumor proliferation is valid.…”
Section: Resultssupporting
confidence: 57%
“…A 23% reduction in the mean Ki-67 proliferative index was observed in the post-treatment tumor (Mean +/– SEM: 10% +/– 1.0) compared to the pre-treatment tumor (Mean +/– SEM: 13% +/– 0.5) ( p = 0.02) (Figure 3B). Given that substantial concordance has been reported for the Ki-67 index between breast cancer core needle biopsies and their respective final surgical specimen [37], we believe this propranolol-mediated statistically significant decrease in tumor proliferation is valid.…”
Section: Resultssupporting
confidence: 57%
“…Identifying HER2-positive breast cancer patients by CNB is important, as neoadjuvant HER2-targeted therapy is an effective option for these patients. In this study, the CR for HER2 status, as determined by HER2 IHC or reflex HER2 SISH, was as high as 99.7% (kappa, 0.988), which was higher than most previous reports (ranging from 61%-97.3%) [10,[18][19][20][21][22][23][24][25][26][27][28][29]. The reason for this high CR could partially be due to performing reflex HER2 SISH for all HER2 IHC equivocal cases to determine final HER2 status strictly following ASCO/CAP guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…29 Purdie et al reported that absent PgR expression was significantly associated with poorer prognosis, even within ER-positive cases. 30 These reports suggests that the assessment of PgR expression in breast carcinomas may still benefit from patient's prognosis. However, it should be noted that most of the treatment response data in previous reports relate to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, the reliability of using CNB specimens for detailed assessment is in doubt because of the relatively small number of cases and differing results between previous studies (Table 1). [20][21][22][23][24][25][26][27][28][29][30][31][32][33] The purpose of this study was to compare the ER, PgR, HER2 status, and Ki-67 index by IHC analysis in breast carcinoma to determine the level of concordance between CNB and surgical specimens.…”
mentioning
confidence: 99%